For the Anniversary of the Union State: Some Economic Parameters and Political Restraints - V. A. Shamakhov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
The article considers some results of economic integration of Russia and Belarus. It is shown that despite all discussions and disputes, a powerful integration core has been formed, the importance of which cannot be overestimated. At the same time, the problems of European integration show us the need to take into account both European and own mistakes. The most serious problem would be stopping integration and ignoring those opportunities provided by the EAEU.